2011
DOI: 10.1063/1.3552484
|View full text |Cite
|
Sign up to set email alerts
|

Surface defects on thin sheets after flanging

Abstract: Several surface defects can develop on automotive exterior panels during the forming operations. They alter the vehicle aesthetic and their severity increases with the decrease of sheet thickness. These defects are difficult to characterize experimentally and reproduce numerically because of their depth below 0.5 mm and the complexity of the parts on which they develop. This study proposes a method that uses curvature of profiles to detect and characterize surface defects. The method has applied to a laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2011
2011

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Analysis of the stress and strain states in the defect area showed that after springback, a stress gradient of bending type was obtained through the thickness, that could lead to a depression [8]; the gradient was much higher with solid than with shell elements.…”
Section: Mesh Sizementioning
confidence: 99%
“…Analysis of the stress and strain states in the defect area showed that after springback, a stress gradient of bending type was obtained through the thickness, that could lead to a depression [8]; the gradient was much higher with solid than with shell elements.…”
Section: Mesh Sizementioning
confidence: 99%